Membangun Spiritualitas Kristen: Sebagai Upaya Menanggulangi Pergaulan Bebas Pada Remaja Masa Kini - Gabriel A. P. Saragih; Windya Permai Br Sirait; Naomi Wahyuni; Merlin Santinus; Sunardi Gani (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Teenage promiscuity is a significant challenge in contemporary society. This article aims to present an approach that integrates Christian spirituality in order to tackle this phenomenon. Through a qualitative method with a focus on literature, we explore the role of spirituality in shaping the character of adolescents and providing positive alternatives in dealing with promiscuity. In-depth analysis of theological and psychological sources shows that spirituality is not only a source of internal strength for adolescents, but also plays an important role in building healthy relationships with oneself, others, and God. The results of this study show that the integration of Christian spirituality can be a strong foundation for adolescents in facing the challenges of promiscuity. The practical implications of the findings are presented as a contribution for educators, parents, and youth leaders in guiding adolescents towards a life based on Christian values.